Short Communication: The physical and chemical properties of nipah (Nypa fructicans) frond as an alternative feed for ruminants in Indonesia - Muhammad Afdal; Teja Kaswari; Saitul Fakhri; Heni Suryani (Society for Indonesian Biodiversity, 2020)
Abstract. Afdal M, Kaswari T, Fakhri S, Suryani H. 2020. Short Communication: The physical and chemical properties of nipah (Nypa fructicans) frond as an alternative feed for ruminants in Indonesia. Biodiversitas 21: 4714-4718. The aim of this study was to evaluate the physical and chemical properties, as well as the degradation of dry matter (DM) and organic matter (OM), of nipah (Nypa fructicans Wurmb.) frond, in view of its potency as an alternative source of feed. Samples of nipah frond were collected from the Sub-district of Geragai and Nipah Panjang, Indonesia, representing lowland brackish and coastal areas, respectively. All samples were explored to reveal their physical and chemical properties, degradation of DM and OM, and total gas production. The t test was applied to compare parameters between the Geragai and Nipah Panjang areas. There were no significant differences (P > 0.05) in frond weight and leaf weight between the two sample locations. The length of frond and the length from base to first leaf of nipah was significantly different (P < 0.05) between both locations. The number of leaves in one frond and the number of fruit in one bunch were highly significant different (P < 0.01) between the two sample regions. The DM and OM degradation of nipah fronds and leaves were not significantly different (P > 0.05). between Geragai and Nipah Panjang, while the DM and OM degradation of nipah leaves were also not significantly different (P > 0.05). However, total gas production from the leaves and fronds were highly significantly different (P < 0.01) between Geragai and Nipah Panjang. It can be summarized that the physical properties and chemical composition of the fronds and leaves of nipah in these areas are similar except for the length between base and the first leaf, the number of leaves, and the number of fruit in a single bunch, which were different. In terms of DM and OM degradation, there were no differences between the lowland brackish area and the coastal area, except for in terms of total gas production, which was significantly different between the two sample locations.